A new species of Rheotanytarsus Thienemann & Bause (Diptera: Chironomidae) from Peruvian Andes, with updated key to South American species - Dantas, Galileu P. S.; Araujo, Ana A. Huamantinco; Hamada, Neusa (Zootaxa, 2020)
Rheotanytarsus is a speciose genus, currently composed by more than 100 nominal species distributed worldwide, 19 are known from the Neotropical region, four from South America and only one is registered for Peru. In the present study, a new species is described and illustrated based on males collected in the Peruvian Andes. In addition, the key to the South American species is updated and a distribution map of them is provided. Rheotanytarsus amaru sp. n. is easily distinguished from the congeneric species by the dark general coloration and the hypopygial morphology.